Ocular Exposure to Particulate Matter and Development of Pterygium: A Case-Control Study - Alberto Ramirez, Carlos (2018)
Background: Formation of pterygium has been mainly attributed to exposure to the ultraviolet (UV) radiation. Other factors such as dry weather, wind exposure and microtrauma with dust particles, have been linked to development of pterygium. Objective: To determine the association between ocular exposure to particulate matter and development of pterygium. Methods: This case-control study was conducted in a company dedicated to the production and marketing of toilets. We included a total of 90 cases identified in November 2013 and 184 controls. The diagnosis of pterygium was based on clinical examination. Variables studied included age and job tenure of the participants. Logistic regression analysis was used to assess the effect of exposure on developing pterygium. Results: All study participants were male. The mean age of the cases and controls was 39.9 (SD 9.5) and 37.8 (SD 7.3) years, respectively. 115 (42%) of the participants had a job tenure of 5–8 years. The percentages of cases and controls exposed to particulate matter were 31.1% (n=28) and 30.4% (n=56), respectively (OR 1.08, 95% CI 0.61 to 1.91). Conclusion: We could not observe any association between ocular exposure to particulate matter and development of pterygium.